PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA VIDEO INTERAKTIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS V - Nur Faizah, Eka; Roestika Rini, Zulmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary students need mathematical problem-solving skills to understand information, plan strategies, execute procedures, and evaluate solutions. Preliminary data at SD Negeri 1 Gondangwayang showed that the average achievement of fifth-grade students on Polya’s problem-solving indicators was only 38%, indicating the need for more active and technology-supported learning. This study examined differences in problem-solving ability and the effect of the discovery learning model assisted by interactive video. A quantitative quasi-experimental method with a nonequivalent control group design was employed. The sample comprised 40 fifth-grade students selected through purposive sampling, with 20 students in the experimental class and 20 in the control class. The experimental class received discovery learning supported by interactive video, whereas the control class received discovery learning without interactive video. Data were collected using essay tests, questionnaires, observation sheets, and student worksheets. The instruments were tested for validity and reliability; the test reliability coefficient was 0.889. Data analysis included Shapiro–Wilk normality tests, Levene homogeneity tests, an independent-samples t-test, and simple linear regression. The experimental class obtained a higher posttest mean than the control class (87.75 versus 68.00). The difference was significant, t(38)=10.503, p<0.000. Regression analysis yielded β=0.862, t=10.503, p<0.000, with R²=0.744. Thus, discovery learning assisted by interactive video significantly improved fifth-grade students’ mathematical problem-solving ability.